2015
DOI: 10.1002/ccd.25769
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary percutaneous coronary intervention in patients withST‐elevation myocardial infarction during and prior to availability of an in‐houseSTEMIsystem: Early experience and intermediate outcomes of theHARRTprogram for achieving routineD2Btimes <60 minutes

Abstract: Availability of an in-house 24-hr STEMI team significantly decreased reperfusion time and led to improved clinical outcomes and a shorter LOS for PCI-treated STEMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…More successful results in door-to-balloon time were detected in studies performed in centers where this parameter has been studied for a longer time, as in the United States, Europe and Asia. 5,15,16 More challenging targets such as a door-to-balloon time shorter than 60 minutes 17 were achieved by some authors such as Mentias et al, 18 who reported a median door-to-balloon time of 38 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…More successful results in door-to-balloon time were detected in studies performed in centers where this parameter has been studied for a longer time, as in the United States, Europe and Asia. 5,15,16 More challenging targets such as a door-to-balloon time shorter than 60 minutes 17 were achieved by some authors such as Mentias et al, 18 who reported a median door-to-balloon time of 38 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Our hospital already implements many of the systems and processes shown to reduce D2B 12,13. Others have shown that having an attending interventional cardiologist on-site 24/7 is associated with shorter D2B times 10,13. This option, however, may be too costly or impractical to sustain for most hospitals with STEMI programs.…”
Section: Discussionmentioning
confidence: 99%
“…Bradley et al10 report data from a web-based survey study focused on STEMI care and found that among the strategies that were associated with lower D2B times, the presence of an attending interventional cardiologist always at the hospital decreased D2B times by a mean of 14.6 minutes. Nguyen et al13 studied the impact of a newly created 24/7 in-house interventional team, including the interventional cardiologist, and found that there was a 57% reduction in D2B time 13. In addition, they also found that differences between regular working hours and off-hours D2B times were completely eliminated 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of CCI , Lopez and coworkers report on the early experience and intermediate outcomes with an “in‐house” STEMI program—the Heart Attack Rapid Response Team (HARRT Program) . They compared the treatment times and clinical outcomes in 59 STEMI patients in the 2 years before implementation of HARRT Program to 61 STEMI patients in the 20 months post‐implementation.…”
mentioning
confidence: 99%